A visão de crianças diagnosticadas com distúrbios de leitura e escrita a respeito dessa queixa - Rosa, Monique Coelho Cassarotti da (2017)
Currently, it has been evidenced high demand for speech language therapeutic follow-up for children presenting difficulties in the written language. In general, literature from the speech language therapeutic field points that children, when questioned, cannot understand why they were referred to the clinic. Many report that they feel frustrated and discouraged in relation to reading and writing practices, as well as with their school life, thus suffering with that. In this sense, this study aimed to analyze subjects’ self-perception regarding the complaint of difficulties in reading and/or writing. It is an exploratory research study carried out in a speech language pathology teaching clinic connected with a Higher Education institution. The sample comprised ten children between six and fourteen years of age, attending between the first and seventh grades of elementary and middle school. All of them were referred to speech language therapy assessment due to complaints of written language difficulties. Data were collected by means of semi-structured interviews and submitted to quantitative and qualitative analysis. Their self-perception on the reason to be referred to clinical assessment was related to: speak wrongly, make spelling mistakes, learn to read and write, not to fail at school, deal with the graphemes. It was evidenced that the subjects considered the cause of their difficulties centered on themselves or organic issues. On the effects of being referred to, the subjects reported negative feelings. The analysis of the enunciates led us to evidence, from a sociohistorical conception and according to studies in the area, that their speeches incorporate social voices unveiling an organicist perspective on the language appropriation, as they associate the complaint about reading and writing difficulties with individual aspects and organic origin. From a sociohistorical perspective, the complaint of reading and writing difficulties is understood and re-meant by means of reflections which consider language historicity, situations with effective use of writing, as well as the social context of verbal interactions where interactions take place, and ultimately involve the self and the other